Nas trincheiras da sobrevivência: a Segunda Guerra Mundial e suas implicações para os trabalhadores no Rio Grande do Sul - Soares, Tamires Xavier (2020)
World War II broke out in 1939, causing transformations around the world, even countries that did not immediately become involved in the conflict felt its implications. At that time, Brazil was in the midst of the dictatorship of the Estado Novo, under the government of Getúlio Vargas. That maintained a policy of neutrality in the face of the war situation until 1942, when it declared a state of war, leading Brazil to fight alongside the Aliados. The reflexes of the war have been felt by Brazilians since 1939, through an increase in the cost of living, a shortage of products and gradual changes in labor relations. Therefore, through this research we seek to understand what were the implications caused by the war to the worker's life in Rio Grande do Sul and the strategies used by them in the face of the situation of mobilization and restrictions experienced since 1939. Keywords